The Productive Zakat in Empowering Mustahik Entrepreneurship - Firmansyah, Yusril; Sukarno, Hari; Masruroh, Nikmatul (The Es Economics and Entrepreneurship, 2024)
Productive zakat is one of the instruments in sustainable development related to Islam. Productive zakat is managed in providing businesses to mustahik, so that mustahik zakat does not receive consumable zakat but can be sustainable. So, this research has objectives, first, to explore the role of productive zakat in mustahik economic empowerment, second, to analyze the pattern or model of productive zakat in mustahik entrepreneurship empowerment. This research was conducted with a qualitative approach through a case study, namely in Probolinggo Regency. Data collection techniques used observation, interviews and documentation. The data were analyzed using the Miles and Huberman interactive model. Data validity used source triangulation and technique triangulation. This research results in, first, productive zakat can contribute to the addition of mustahik income and break the chain of mustahik dependence on muzakki, second, productive zakat can empower mustahik entrepreneurship through the Z-Chicken, Z-Auto, the livestock and Batik Craftsmen programs. These programs are able to improve mustahik skills, so that mustahik have an entrepreneurial spirit for sustainable economic development.